Dynamical formation of the GW190814 merger - Arca Sedda, Manuel (The astrophysical journal. Part 2, Letters, 2021)
We investigate the possible dynamical origin of GW190814, a gravitational wave (GW) source discovered by the LIGO-Virgo-Kagra collaboration (LVC) associated with a merger between a stellar black hole (BH) with mass 23.2 M ⊙ and a compact object, either a BH or a neutron star (NS), with mass 2.59 M ⊙. Using a database of 240,000 N-body simulations modeling the formation of NS-BH mergers via dynamical encounters in dense clusters, we find that systems like GW190814 are likely to form in young, metal-rich clusters. Our model suggests that a little excess (∼2%-4%) of objects with masses in the range of 2.3-3 M ⊙ in the compact remnants’ mass spectrum leads to a detection rate for dynamically formed “GW190814 -like” mergers of ΓGW190814 ≃ 1-6 yr−1 Gpc−3, i.e., within the observational constraints set by the GW190814 discovery, ΓLVC ∼ 1-23 yr−1 Gpc−3. Additionally, our model suggests that ∼1.8%-4.8% of dynamical NS-BH mergers are compatible with GW190426_152155, the only confirmed NS-BH merger detected by the LVC. We show that the relative amount of light and heavy NS-BH mergers can provide clues about the environments in which they developed.
Gesehen am 26.03.2021